2010
DOI: 10.1177/1477370810363374
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for delinquency in adolescent and young adult females: A European review

Abstract: This article reviews 30 European studies on risk factors for delinquency in adolescent and young adult females. Risk factors are compared with those for (adolescent) male delinquency. Risk factors unique to females are identified, as well as risk factors shared by males and females. Sex differences in risk factors are mainly found for individual and family factors. Females and males differ less in school and peer risk factors. As studies zoom in more on specific domains of risk factors or specific types of del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 34 publications
5
58
1
6
Order By: Relevance
“…In accordance with differential association theory, studies have shown similar effects of delinquent attitudes on delinquency across sexes (Mears et al 1998;Piquero et al 2005). However, although most previous studies indicated that the association between delinquent peers and delinquent behavior are similar for boys and girls (see Hubbard and Pratt 2002;Wong et al 2010), few studies found sex differences in the effect of peer delinquency on delinquency (Mears et al 1998;Piquero et al 2005). Mears et al (1998) found that boys were more strongly affected by delinquent peers than girls.…”
Section: Sex Differences In Indirect Pathways From Parenting To Delinmentioning
confidence: 77%
See 1 more Smart Citation
“…In accordance with differential association theory, studies have shown similar effects of delinquent attitudes on delinquency across sexes (Mears et al 1998;Piquero et al 2005). However, although most previous studies indicated that the association between delinquent peers and delinquent behavior are similar for boys and girls (see Hubbard and Pratt 2002;Wong et al 2010), few studies found sex differences in the effect of peer delinquency on delinquency (Mears et al 1998;Piquero et al 2005). Mears et al (1998) found that boys were more strongly affected by delinquent peers than girls.…”
Section: Sex Differences In Indirect Pathways From Parenting To Delinmentioning
confidence: 77%
“…It is, however, possible that boys and girls differ in risk factors for delinquency that were not included in the present study. For example, previous research has indicated that negative life events, physical abuse by parents, and internalizing problems were risk factors for girls but not for boys (Wong et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical findings support the connection between peers' delinquency and the youths own delinquent behavior, where deviant peers both expose youths to criminal activities as well as encourage such behavior (Brauer and De Coster, 2015;Farrington, Ttofi & Coid, 2009;Haynie, 2002;Warr, 2002;Wike, Miller, Winn, & Taylor, 2013;Worthen, 2012). Meta analyses of the predictors of juvenile delinquency have found that deviant peers are a major risk factor for adolescents (Wong, Slotboom, & Bijleveld, 2010), and a deviant peer group has been shown to be one of the strongest predictors of female delinquency (Hubbard & Pratt, 2002), even when parents, school and other interpersonal factors are controlled for (Pleydon & Schner, 2001).…”
Section: Introductionmentioning
confidence: 85%
“…Like Moffitt et al (2002) we found that earlier age of crime onset is generally accompanied by higher psychopathy traits. We are not stating that higher psychopathic traits trigger earlier age of onset, but these two variables may be reinforcing each other alongside other variables like negative life events, substance abuse, inadequate parenting, low attachment to school or having delinquent friends (Wong et al, 2010), to produce life course persistent female offenders.…”
Section: Discussionmentioning
confidence: 99%